ANALISIS FAKTOR HOSPITALITY MASYARAKAT TERHADAP WISATAWAN DI KAWASAN WISATA PULAU PENYENGAT KOTA TANJUNG PINANG PROPINSI KEPULAUAN RIAU - Kawakibi Pristiwasa, I Wayan Thariqy; Augustinus, Daniel Cassa (Journal of Accounting and Management Innovation, 2017)
This study aims to find factor analysis of components that create community hospitality in tourist areas of the Penyengat island of Tanjung Pinang town in Riau Archipelago Province which are in the form of resources and social culture. This study uses qualitative descriptive research regarding the concept of tourism and hospitality population in this study is a form of social situation in the Penyengat Island with participants that are inside that community, tourists and institutional as well as tourism industry players in the region. Instruments in this study are observation and interviews. The interview is conducted with model of coding, interpretation and congrulation. These results indicate that the factor analysis of the hospitality community rating which consists of resources and socio-cultural community, institution or organization in the Penyengat Island.Keywords: tourism, community, tourism industry, institutional